Raw output files generated by the mothur program - Galan, Maxime; Razzauti, Maria; Bard, Emilie; Bernard, Maria; Brouat, Carine; Charbonnel, Nathalie; Dehne-Garcia, Alexandre; Loiseau, Anne; Tatard, Caroline; Tamisier, Lucie; Vayssier-Taussat, Muriel; Vignes, Hélène; et al. (Dryad Digital Repository, 2016)
This ZIP file contains seven output files (.groups, .names, .table, .taxonomy, .list, .fasta and .log) generated by the mothur program for the whole 16S rRNA dataset. The .log file contains all the mothur command lines used for the processing of the raw sequences.